Prospective validation of %p2PSA and the Prostate Health Index, in prostate cancer detection in initial prostate biopsies of Asian men, with total PSA 4-10 ng ml-1 - Lincoln GL Tan; Yung Khan Tan; Bee Choo Tai; Karen ML Tan; Vineet Gauhar; Ho Yee Tiong; Robert CW Hawkins; Thomas P Thamboo; Felicia SK Hong; Edmund Chiong (Asian Journal of Andrology, 2017)
Despite its widespread use for prostate cancer screening, low specificity makes PSA a suboptimal biomarker, especially in the diagnostic "gray zone" of 4-10 ng ml-1 . False-positives lead to unnecessary biopsies with attendant morbidities. This is the first prospective validation study of %p2PSA and the Prostate Health Index (PHI) in Asian men presenting with a total PSA between 4.0 and 10 ng ml-1 . We studied 157 Asian men between 50 and 75 years old, with normal per rectal prostate examinations, undergoing their first prostate biopsy, using a standardized biopsy protocol, for PSA levels of 4-10 ng ml-1 . Thirty (19.1%) were found to have prostate cancer on biopsy. Statistically significant differences between patients with and without prostate cancer were found for total PSA, p2PSA, %p2PSA, and PHI. The areas under the curve of the receiver operating characteristic curve for total PSA, %fPSA, %p2PSA, and PHI were 0.479, 0.420, 0.695, and 0.794, respectively. PHI predicts prostatic biopsies results best. At a sensitivity of 90%, the specificity (95% CI) of PHI was 58.3%, more than triple the specificity of total PSA at 17.3%, potentially avoiding 77 (49%) unnecessary biopsies. Similar to studies in mainly Caucasian populations, we have prospectively shown that %p2PSA and PHI greatly outperform total and free to total PSA ratio, in the detection of prostate cancer at first biopsy. Higher PHI levels also correspond to increasing the risk of detecting GS ≥7 cancers. We have validated the use of PHI to aid decision-making regarding prostate biopsies in Asian men with serum PSA between 4 and 10 ng ml-1 .